IMPLEMENTASI PROGRAM PENARIKAN PEKERJA ANAK – PROGRAM KELUARGA HARAPAN (PPA-PKH) DI KABUPATEN MAGELANG - Dewi Rostyaningsih (GEMA PUBLICA : Jurnal Manajemen dan Kebijakan Publik, 2015)
Children is an investment of the nation in carrying out development. Theyneed to get protection in accordance with the rights of the child. In Indonesiathere are still many children who work in hazardous places for their developmentso that their rights are not being met. To reduce the number of child workers, thegovernment made a reduction program in child labor in very poor householdscalled Withdrawal of Child Labor Program Family Hope Program (PPA-PKH). Theresearch objective is to describe the implementation of PPA-PKH program inMagelang and analyze the push and pull factors program. This study used aqualitative approach, with data analysis techniques include data reduction,presentation, conclusions and verification.Implementation of PPA-PKH program includes productivity, linearity andefficiency. The results showed that the productivity of children who return toschool only 60%. Linearity views of conformity procedures, time, cost, place andimplementing many are not appropriate. The efficiency has been achieved inimplementing the empowerment resources and assets, whereas for the utilizationof funds and technology are still less efficient. The push factors are include thesubstance of the policies and behavior of implementor, while the pull factors,interaction networks, the participation of target groups and resources; as well asother factors include a lack of awareness of parents and school attitudes thatwere not receiving target.Implementation of PPA-PKH program in Magelang District has not gonewell. Recomendation submitted in the implementation of the PPA-PKH include:data collection target group, the timely implementation, coordination betweenteam PPA-PKH and implementation team, increased oversight of funds, anincrease in facility premises, facilities and infrastructure, as well as assistingparents to raise awareness parents of the importance of school for the future oftheir children.Keywords : implementation, productivity, linearity, efficiency, push and pullfactors.